ASSESSMENT OF SENIOR DENTAL STUDENTS AND DENTAL RESIDENTS IN MATTERS OF ANTIMICROBIAL CHEMOTHERAPY - Roman Bontsevich; Kristina Shchurovskaya; Tatyana Pokrovskaya; Larisa Goryainova (Belgorod National Research University, 2015)
Antimicrobial therapy (AMT) is one of the principal problems in practice of the modern dentist. Mass visits to doctors for dental care, the prevalence of dental diseases among people from all walks of life, a unique quantitative and qualitative composition of the oral microflora, uncontrolled use of antimicrobials by patients results in increased resistance of microorganisms to antimicrobial medicines and increased number of cross-infection among dental office visitors. This article highlights the results of the study designed to assess knowledge of senior dental students of medical schools and dental residents on the main issues of antibiotic therapy and the empirical use of antimicrobials for treatment of respiratory disorders. Dental students of Belgorod have come into the study. According to the inquiry, 21.2% of dental students and 12.8% of dental residents were able to correctly choose the pharmacological group of antibiotics. 47.5% of students and 43.8% of residents decided to change the antibiotic due to the absence of clinical response within two to three days. 35% of dental students and 37.5% of the dental residents re-inquired believe that antibiotics should be replaced even in case of the positive result from their use. 16.7% of dental students managed to correctly choose all pharmacologically irrational combinations of antimicrobials, 17.2% of dental residents answered correctly after having been re-inquired. 25.6% of students and 31.2% of residents managed to completely make the empirical assignment of the AMT in case of respiratory infection. Only 50% of students and 62.5% of residents decided that their knowledge of the AMT is insufficient for the future work in the field of health care, and they need to make additional educational efforts related to the topic.